2015
DOI: 10.1093/mnras/stv1342
|View full text |Cite
|
Sign up to set email alerts
|

A near-infrared survey of the inner Galactic plane for Wolf–Rayet stars – III. New methods: faintest WR stars

Abstract: A new method of image subtraction is applied to images from a J, K, and narrow-band imaging survey of 300 deg 2 of the plane of the Galaxy, searching for new Wolf-Rayet stars. Our survey spans 150 • in Galactic longitude and reaches b = ±1 • with respect to the Galactic plane. The survey has a useful limiting magnitude of K = 15 over most of the observed Galactic plane, and K = 14 (due to severe crowding) within a few degrees of the Galactic centre. The new image subtraction method described here (better than … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…This was identified as a WR star by Kanarek et al (2015), who classified it WC8. It brightened in W1 and W2 between the All-Sky and Post-Cryo survey observations (Table 14, Fig.…”
Section: Wr 122-14 = Ksf14 1553-15dfmentioning
confidence: 99%
“…This was identified as a WR star by Kanarek et al (2015), who classified it WC8. It brightened in W1 and W2 between the All-Sky and Post-Cryo survey observations (Table 14, Fig.…”
Section: Wr 122-14 = Ksf14 1553-15dfmentioning
confidence: 99%
“…A three-color composite image of the G34.260+0.169 region (hereafter G34) is shown in Figure 3. This region hosts a WC8-type W-R star, 1553-15DF (Kanarek et al 2015). Wang et al (2016) reported the presence of a gaseous filament, F36, at a distance of 1.6 kpc projected toward this region.…”
Section: G34260+0169mentioning
confidence: 97%
“…The G51.840+0.410 region (hereafter G51) harbors a W-R star, 1697-38F, which is classified as WC9 (Kanarek et al 2015) and hosts two MIR bubbles, N108 and N109 (see Figure 5). Bania et al (2012) noted star formation toward the edge of N109, and identified this as one of the largest H ii regions in the Milky Way.…”
Section: G51840+0410mentioning
confidence: 99%
See 1 more Smart Citation
“…It is a radio and millimetre source and has been listed as a PN (Urquhart et al 2009). In a survey of the inner GP for Wolf-Rayet stars, Kanarek et al (2015) also class this object as a possible PN (object 1527-318B); their near-infrared spectrum shows strong emission from Hei (2.058 µm) and Br γ which can be characteristic of young PNe (e.g. Gledhill & Forde 2015).…”
Section: Colourmentioning
confidence: 99%